Epidermal barrier abnormalities in exfoliative ichthyosis with a novel homozygous loss‐of‐function mutation in CSTA. (18th March 2015) - Moosbrugger‐Martinz, V.; Jalili, A.; Schossig, A.S.; Jahn‐Bassler, K.; Zschocke, J.; Schmuth, M.; Stingl, G.; Eckl, K.M.; Hennies, H.C.; Gruber, R.
Summary Autosomal recessive exfoliative ichthyosis (AREI) results from mutations in CSTA, encoding cysteine protease inhibitor A (cystatin A). We present a 25‐year‐old man from Iran with consanguineous parents, who presented with congenital erythroderma, hyperhidrosis and diffuse hyperkeratosis with coarse palmoplantar peeling of the skin, aggravated by exposure to water and by occlusion. Candidate gene analysis revealed a previously unknown homozygous loss‐of‐function mutation c.172C>T (p.Arg58Ter) in CSTA, and immunostaining showed absence of epidermal cystatin A, confirming the diagnosis of AREI. Ultrastructural analysis by transmission electron microscopy showed normal degradation of corneodesmosomes, mild intercellular oedema in the spinous layer but not in the basal layer, normal‐appearing desmosomes, and prominent keratin filaments within basal keratinocytes. Thickness of cornified envelopes was reduced, lamellar lipid bilayers were disturbed, lamellar body secretion occurred prematurely and processing of secreted lamellar body contents was delayed. These barrier abnormalities were reminiscent of (albeit less severe than in) Netherton syndrome, which results from a deficiency of the serine protease inhibitor LEKTI. This work describes ultrastructural findings with evidence of epidermal barrier abnormalities in AREI.